1961
DOI: 10.1177/004051756103100805
|View full text |Cite
|
Sign up to set email alerts
|

Wool Fabric Stabilization by Interfacial Polymerization. Part I: Polyamides

Abstract: A new technique is presented for making wool fabrics shrink resistant. Through interfacial polymerization polyamides, e.g., poly (hexamethylene sebacamide), are formed on the surface of the textile fibers. Fabric is padded consecutively through an aqueous solution of a diamine and a water-immiscible solution of a diacid chloride. Polymerization is extremely rapid and no heating or curing is required. Following the two-step padding, the fabric is simply washed and dried. Less than 5% resin on the fabric is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

1966
1966
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…sebacoyl chloride) dissolved in a water-immiscible solvent. A polyamide polymer coating is formed at the interface of the two liquid phases through interfacial condensation polymerization, which is similar to the process developed by Whitfield et al [73]. The key advantage is the very low energy consumption for the treatment and also the absence of damage to the outer layer of wool.…”
Section: Subtractive Treatments Based On Partial/full Removal Of Cutimentioning
confidence: 99%
See 1 more Smart Citation
“…sebacoyl chloride) dissolved in a water-immiscible solvent. A polyamide polymer coating is formed at the interface of the two liquid phases through interfacial condensation polymerization, which is similar to the process developed by Whitfield et al [73]. The key advantage is the very low energy consumption for the treatment and also the absence of damage to the outer layer of wool.…”
Section: Subtractive Treatments Based On Partial/full Removal Of Cutimentioning
confidence: 99%
“…A range of crosslink forming polymeric resins, such as, polybutadiene [68], polyurethane containing free isocyanate groups (Synthappret LKF) [69], polyurethane with bisulfite adduct (Synthappret BAP) [70], Bunte-salt terminated polyether (Lankrolan SHR3) [71], polythiols [72], polyamides by interfacial polymerization [73], polydimethylsiloxane diols in combination with an amino functional silane crosslinking agent [74], diacrylates [75], have been investigated to form polymeric coating on wool fiber. Cook and Fleischfresser reported that wool fabrics coated with bisulfite-adduct named Synthapret BAP at 3.0% owf provided excellent shrink-resistance but considerably affected the handle properties of the treated fabric [70].…”
Section: Subtractive Treatments Based On Partial/full Removal Of Cutimentioning
confidence: 99%
“…Many methods have been developed for preventing shrinkage of wool fibers, and they can be classified into three main categories. The first is coating with resins such as polyamide epichlorohydrin or grafting polymers onto wool fibers [ 1,3,4,14]. The second is morphological modification of the cuticular cells by chemical or physical treatment [2,8,13].…”
mentioning
confidence: 99%
“…This is designated brieHy as &dquo;steam.&dquo; Interfacial polyureri~crtion.' This was carried out by using he}Glmethylenediamine, sodium carbonate, and a wetting agent in the first or aqueous bath, and sebacoyl chloride dissolved in Stoddard solvents in the second bath (according to Whitfield, Miller, and . Wasley [18]). The wet pickup after the aqueous bath was reduced to 50% by squeezing in pad rolls and drying in air.…”
Section: Introductionmentioning
confidence: 99%
“…' Interfacial polymerization. Nylon 66 was applied as described in the text [18]. Polyurethane [ 19 ] was applied with a first and aqueous bath of 2% hexhmethylene diamine, 4% sodium carbonate, and 0.1 ~o Triton X-100 (Rohm and Haas).…”
Section: Introductionmentioning
confidence: 99%